2005
DOI: 10.1007/s10344-005-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Urgent call for further breeding of the relic zoo population of the critically endangered Barbary lion (Panthera leo leo Linnaeus 1758)

Abstract: Urgent call for further breeding of the relic zoo population of the critically endangered Barbary lion (Panthera leo leo Linnaeus 1758) Abstract The Barbary lion became extinct in the wild around 1942. Since the end of the 19th century, a last purebred captive breeding stock existed at the court of Morocco. The rest of these animals became the core exhibition of the new Rabat Zoo after passing through repeated bottlenecks and possibly some introgression events by foreign lions. This study uses mitochondrial DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…4), and the F-matrix also indicated that they were distinctly different from the two other South African lions, P. l. bleyenberghi and P. l. krugeri, as well as all other lions. The canonical variable plot and the Fmatrix values indicate that the Asiatic lion is the most aberrant, in accordance with it traditionally being considered a more primitive type of lion along with the Barbary lion and Cape lion (Hemmer 1974), which has recently been corroborated by genetic analyses (Burger et al 2004;Burger and Hemmer 2006). CN1570 groups distinctly away from other lions, and tends towards the Cape lions.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…4), and the F-matrix also indicated that they were distinctly different from the two other South African lions, P. l. bleyenberghi and P. l. krugeri, as well as all other lions. The canonical variable plot and the Fmatrix values indicate that the Asiatic lion is the most aberrant, in accordance with it traditionally being considered a more primitive type of lion along with the Barbary lion and Cape lion (Hemmer 1974), which has recently been corroborated by genetic analyses (Burger et al 2004;Burger and Hemmer 2006). CN1570 groups distinctly away from other lions, and tends towards the Cape lions.…”
Section: Resultsmentioning
confidence: 52%
“…A key feature in the subspecific proposition of the Amsterdam specimen was the appearance of the mane, as seen in a painting ( Van Bree 1998), but the Barbary lion (Panthera leo leo) also has a large, heavy mane and a well-developed belly mane (e.g., Mazak 1964bMazak , 1970Hemmer 1974). Additionally, since the Barbary lion has recently been shown to be related to the Asiatic lion (Burger et al 2004;Burger and Hemmer 2006), this raises further doubts about the Amsterdam specimen. If this animal is, in fact, a Barbary lion, then the limb bones figured in this paper are the only postcranial remains known from a probable Cape lion.…”
Section: Article In Pressmentioning
confidence: 94%
“…Therefore, ex situ conservation of genetic diversity is becoming a topic of increasing importance as it may preserve the genetic diversity of species until reintroduction programmes can be successfully implemented (see, e.g., Henry et al (2009) for an example on the critically endangered Amur tiger). It has been argued that the genetic heritage of some lion populations extinct in the wild, such as the Barbary lion, may at least partially be preserved in captive populations (Barnett et al 2006b;Burger and Hemmer 2006;Black et al 2010). However, given the limited information on the phenotypes and especially genetics of now extinct populations, appreciable genetic diversity may already have been lost in the lion.…”
Section: Discussionmentioning
confidence: 98%
“…The genetic distinctiveness of the historical Barbary lion has not yet been fully established and the question over whether the Royal Lions are true Barbary lions remains unanswered Yamaguchi 2005;Barnett et al 2006b;Burger and Hemmer 2006;Antunes et al 2008). However, the historical Barbary lion is morphologically more distinct than any of the African lion populations (Hemmer 1978), so the guidelines of the precautionary principle (Foster et al 2000) would suggest that reasonable action to conserve diversity is preferable.…”
Section: Introductionmentioning
confidence: 94%